Analisis Biaya Penanganan Jalan Nasional Berdasarkan Kondisi Kerusakan Jalan dan Modulus Efektif Perkerasan: Studi Kasus: Ruas Jalan Nasional 017.11(K) Jalan By Pass Demak - , FEMY ARIZONA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Selection method of pavement distress improvement in Indonesia are often less precise. Pavement distress improvement with an overlay that is calculated based on effective modulus of the pavement is often chosen as a quick solution to repair pavement distress. The improvement of structural distress can not be carried out only with the overlay, but necessary structural repairs of the pavement, if this is not done then the new pavement will deteriorate quickly. It became one of the causes of the national road maintenance unit costs are always rising and higher than international standards. World Bank (2011) suggested that the unit cost of road maintenance in Indonesia has become one of the highest in the world. Roads in Indonesia also has a pattern of repeated deterioration (type and location of the deterioration the same), this is caused by the error survey to identify the type and severity of road damage as a first step to determine the repair option. Research carried out by conducting a the condition survey of the pavement distress on road number 017.11 (K) by-pass Demak road to identify the type of distress, the severity and quantity of distress. The survey results were analyzed using the PCI method to determine repair options and calculate costs needs of the repair option, and then compared with the overlay costs are analyzed based on the effective modulus of the pavement with AASHTO method (1993) as well as overlay costs are analyzed by the method of Bina Marga (2005). The calculation of thick overlay of AASTHO (1993) method and Bina Marga (2005) method are base on the deflection test conducted by fallling Weight deflectometer (FWD). The calculation result shows that the ratio between routine maintenance costs and overlay costs of AASHTO (1993) method is 0.71%, the ratio between reconstruction costs and overlay costs of AASHTO (1993) method is 214.44% for 017.11(K) link numbers the by-pass Demak roads, Kudus direction, whereas for Semarang direction shows that ratio between routine maintenance costs and overlay costs of AASHTO (1993) method is 2,55%, the ratio between reconstruction cost and overlay costs of AASHTO (1993) method is 224, 03%. The ratio between routine maintenance costs and overlay costs of Bina Marga (2005) method is 0.78%, the ratio between reconstruction costs and overlay costs of Bina Marga (2005) method is 321.50% for 017.11(K) link number by pass Demak roads, Kudus direction, whereas for Semarang direction shows that ratio between routine maintenance costs and overlay costs of Bina Marga (2005) method is 2.81%, the ratio between reconstruction costs and overlay costs of Bina Marga (2005) method is 324, 67%. The results of this study are expected to be taken into consideration in determining the road maintenance program, so that the forward method of treating distress roads become more precise and optimal. Keywords: pavement distress, effective modulus of the pavement, overlay